Serum haptoglobin levels in patients with active and inactive rheumatic fever - Meriç, Nurten; İleriye, Dilber and Kaçar, Murat and Özkan, Kemal (The Turkish Journal of Pediatrics, 1983)
Utilizing the Sephadex-100 gel filtration technique, haptoglobin levels were determined in specimens taken from 20 patients with active and 37 patients with inactive rheumatic fever, and these groups were matched with 21 normal subjects of the same ages who served as controls. A definite elevation in serum haptoglobin levels (mean: 319 mg ± 180) was noted in the active rheumatic group, but serial determinations revealed that in the early inactive stage of the disease serum haptoglobins (82 mg ± 44.1) were still above the normal values (52 mg ± 26.1). Normal haptoglobin levels were obtained within two to four months after the onset of the disease. From a clinical point of view, it is probable that the normalization of the haptoglobin level may be a reliable indicator of the complete inactivity of the disease.